1990
DOI: 10.1007/s0054000040155
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of intravenous administration of Ringer’s lactate, Ringer’s acetate and 5% glucose containing these Ringer’s solutions in human being

Abstract: The effects of the administration of Ringer's lactate (L) and Ringer's acetate (A) solution on blood biochemistry in human subjects operated for tympanoplasty under general anesthesia were investigated. And the feasibilities of the clinical use of Ringer's lactate (LD) and Ringer's acetate (AD) solution containing 5% glucose were also assessed. In all cases the rate of infusion was 500 ml for initial 20 min, and then 5 ml.hr(-1).kg(-1) B.W. for 3 hr and 10 min. There were significant increases in blood L- and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

1994
1994
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 9 publications
0
2
0
1
Order By: Relevance
“…Ogawa et al [8] and Tabo et al [9] also reported that glucose administration, at the rate of 0.25 g.kg-~.h *, as a link in intraoperative fluid therapy, did not cause an extra rise in blood sugar and was an efficient energy supply. Kuze et al [10] found that Ringer's solution containing glucose, especially given in large amounts, seemed to affect the metabolism, and they recommended that the dose and the infusion rate should be adjusted to avoid metabolic changes. The results of the present study indicate that if the administration rate is 0.2g-kg-~.h -1 or less, glucose may be given during major surgery without the risk of overload.…”
Section: Discussionmentioning
confidence: 99%
“…Ogawa et al [8] and Tabo et al [9] also reported that glucose administration, at the rate of 0.25 g.kg-~.h *, as a link in intraoperative fluid therapy, did not cause an extra rise in blood sugar and was an efficient energy supply. Kuze et al [10] found that Ringer's solution containing glucose, especially given in large amounts, seemed to affect the metabolism, and they recommended that the dose and the infusion rate should be adjusted to avoid metabolic changes. The results of the present study indicate that if the administration rate is 0.2g-kg-~.h -1 or less, glucose may be given during major surgery without the risk of overload.…”
Section: Discussionmentioning
confidence: 99%
“…Выбор именно этих соединений связан с тем, что их метаболизм в меньшей степени зависит от функции печени, поскольку осуществляется, в том числе, в скелетных мышцах [49]. Немаловажным явля ется также тот факт, что ощелачивающее действие аце тата начинается уже через 10-15 мин после внутривенного введения, что связано с его более быст рым метаболизмом по сравнению с лактатом [50]. До полнительным же достоинством малата следует счи тать то, что, являясь естественным метаболитом цикла трикарбоновых кислот, он обладает антиоксидантны ми и антигипоксантными свойствами [51,52].…”
Section: «постоянство внутренней средыоснова свободной жизни» клод беunclassified
“…There has been considerable controversy regarding glucose administration during the intraoperative period, since glucose easily exacerbates carbon dioxide production and intracellular lactic acidosis caused by surgical stress [1]. However, in many circumstances, intraoperative glucose administration may be advantageous to inhibit catabolism and improve fat and carbohydrate metabolism [2][3][4]. Our previous animal study also showed that intraoperative glucose supplementation is effective in preventing hepatic glycogen depletion, and indicated further that the optimal dose to avoid glucose overloading was 0.1-0.2 g·kg Ϫ1 ·h Ϫ1 [5].…”
Section: Introductionmentioning
confidence: 99%